2019
DOI: 10.1177/1077699019866432
|View full text |Cite
|
Sign up to set email alerts
|

Second Screening and the Engaged Public: The Role of Second Screening for News and Political Expression in an O-S-R-O-R Model

Abstract: Second screening has become a prevalent media consumption behavior. Nevertheless, the political implications of second screening are not fully understood. Using data from a two-wave panel survey in Hong Kong, this study examines the role of second screening in contributing to an engaged public based on the Orientation-Stimulus-Reasoning-Orientation-Response (O-S-R-O-R) model. In addition, second screening behaviors are differentiated into second screening for news and for expression. The findings show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The idea behind the development of this model was to suggest a theoretical framework helpful in exploring the indirect effects of different political constructs. Researchers across the world have tested this model in different situations and political backgrounds (Ardèvol-Abreu et al, 2017;Chen, 2019;Jung et al, 2011;Park, 2019). Currently, this model is being tested in other domains of research such as health and environmental communication (Ikhlaq & Ans, 2021;Lu, 2021).…”
Section: O-r-o-r Framework and Proposed Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea behind the development of this model was to suggest a theoretical framework helpful in exploring the indirect effects of different political constructs. Researchers across the world have tested this model in different situations and political backgrounds (Ardèvol-Abreu et al, 2017;Chen, 2019;Jung et al, 2011;Park, 2019). Currently, this model is being tested in other domains of research such as health and environmental communication (Ikhlaq & Ans, 2021;Lu, 2021).…”
Section: O-r-o-r Framework and Proposed Modelmentioning
confidence: 99%
“…In this model, R1 shows expressive/reasoning behavior having characteristics of mental elaboration. Based on previous work (Chen, 2019;Park, 2019), this study situates political discussion as reasoning. It refers to offline and online discussions related to political affairs (McNair, 2003).…”
Section: H4mentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have found multiscreening especially predicts online political expression, such as tweeting during debates, following a reporter, or posting videos (Gil de Zuñiga & Liu, 2017;Maruyama et al, 2014;Vaccari et al, 2015). Recent research has found that active, engaged second screening, which includes discussion and opinion expression, can facilitate political learning as well as political participation (Chen, 2019). Regarding opinion change, multiscreeners who are more politically engaged are more likely to reconsider their political positions or switch their vote choice (Barnidge et al, 2017;Maruyama et al, 2014).…”
Section: Multiscreeningmentioning
confidence: 99%
“…Still however, several underlying mechanisms that work to stimulate participation remain to be explored. First, most research employing the model assesses conventional and institutional forms of participation, targeted at the political sphere (e.g., Chan et al, 2017;Chen, 2019), while only few studies include forms of civic participation targeted at collective or community issues (Muñiz et al, 2017), which is the focus of this study. Second, as SNS are increasingly being acknowledged as platforms and tools for collective action, our study includes SNS participation as an independent mode of participation (Oser et al, 2013;Theocharis and van Deth, 2018b).…”
Section: Introductionmentioning
confidence: 99%